Abriendo Puertas: Evaluation of a Parent Education Program for Latinos. Issue 2 (May 2019) - Caal, Selma; Moore, Kristin; Murphy, Kelly; Lawner, Elizabeth; Rojas, Angela; DeMand, Alex
This study examined the impact of the Abriendo Puertas parent education program among a large sample of low-income, Latino parents and caregivers of preschool children. In all, 922 parents were randomly assigned to the program ( n = 468) or a waitlist control group ( n = 454). Pretest data and posttest data (5-6 weeks postintervention) from parents (86.4% response rate) were collected from both the treatment and control groups. At each time point, parents reported on their knowledge, attitudes, and behaviors related to enhancing their children's school readiness. Confirmatory factor analyses were conducted to assess the factorial validity of each survey scale, and path analyses were conducted to compare the outcomes of the treatment and control groups. In addition, to assess fade-out of program affects among treatment parents, follow-up data were collected 3 months postintervention. Intent-to-treat analyses found that, compared with the control group, the treatment group adopted parenting practices that enhanced preschool children's preparation for school, gained knowledge about high-quality early child care and education settings, improved their ability to set goals for their children, and gained an appreciation for their role as models for their children. No differences were found between the control and treatment groups on parenting practices related to emotional expression, parental advocacy, or healthy behaviors. Results indicate that the Abriendo Puertas program improved parents' and caregivers' knowledge, attitudes, and behaviors. Results of this evaluation help build the evidence base on culturally relevant parenting programs for Latino parents of preschoolers.